Cultivation of Horticultural Plants Based on Hydroponic NFT System using a Portable Greenhouse in Sidomulyo Village, Langkat - Sebayang, Nur Ulina Warnisyah; Benny Hidayat; Sipayung, Antonio Marro; Sinamo, Karina Nola (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Various land use change phenomena have occurred from time to time, especially in Sidomulyo Village, Stabat District. Changes in land use are occurring in line with the increasing population, which has a direct impact on the increasing need for land, especially agricultural land. Sidomulyo Village is located in the urban area of Stabat City, so according to government regulations regarding land use, Sidomulyo Village must be dominated by community settlements, not agricultural land. For this reason, the USU Community Service team offered a solution to continue to be able to carry out agricultural cultivation on limited land, namely the use of the NFT hydroponic system using an easy-to-use portable greenhouse. This cultivation only requires a small amount of land to cultivate horticultural vegetables. The aim of this activity is to develop an NFT system for hydroponic-based horticultural cultivation in Sidomulyo Village so that the community in Sidomulyo Village, Stabat District, becomes an economically and socially independent community and can become a role model for other farmer groups. The next planned stage that must be carried out is monitoring and evaluating the development of horticultural vegetable cultivation through to harvesting and post-harvest handling.